Análisis para Detectar Amenazas y Vulnerabilidades en la red del GAD Municipal de Babahoyo de la Ciudad de Babahoyo - Muñoz Macias, Amanda Julexy (2020)
At present, information security is a topic of vital importance for public sector companies, which is why wireless networks must have adequate administration, because it is one of the most used communication technologies today because it is incorporated on most mobile devices, laptops and computers. The Decentralized Autonomous Government of the Babahoyo canton provides public services through different processes of which the vast majority are managed through information technologies. The problem that exists in the municipality of the city of Babahoyo is that there is no adequate control that protects the security of the equipment, resources and information that is managed in the data network present in the institution. The objective of this case study is to identify the existing vulnerabilities in the network of the municipal GAD of the Babahoyo canton, to proceed to know the possible threats that may threaten the security of the information managed in the institution. The present case study presents a qualitative methodological approach, since it wishes to qualify the state of the network through a network scan using the OpenSource NMap test tool. The security policy that the Babahoyo GAD has to implement must contain a reaction plan for network attacks and security incidents. This policy must determine the responses to various types of incidents, actions for different attacks on the network.